NKp46 is a diagnostic biomarker and may be a therapeutic target in gastrointestinal T-cell lymphoproliferative diseases: a CELAC study. Issue 8 (17th November 2018) - Cheminant, Morgane; Bruneau, Julie; Malamut, Georgia; Sibon, David; Guegan, Nicolas; van Gils, Tom; Cording, Sascha; Trinquand, Amélie; Verkarre, Virginie; Lhermitte, Ludovic; Brousse, Nicole; Jannot, Anne-Sophie; et al.
Abstract : Objectives: Primary GI T-cell lymphoproliferative diseases (T-LPD) are heterogeneous entities, which raise difficult diagnosis and therapeutic challenges. We have recently provided evidences that lymphomas complicating coeliac disease (CD) arise from innate-like lymphocytes, which may carry NK receptors (NKRs). Design: NKRs expression was compared by flow cytometry in intraepithelial lymphocytes (IEL) from CD, type I or type II refractory CD (RCD). NKp46 was next assessed by immunohistochemistry in paraffin-embedded biopsies from 204 patients with CD, RCDI, RCDII or GI T-cell lymphomas and from a validation cohort of 61 patients. The cytotoxic properties of an anti-NKp46 monoclonal antibody conjugated to pyrrolobenzodiazepine (PBD) was tested ex vivo in human primary tumour cells isolated from fresh duodenal biopsies. Results: NKp46 (but not CD94, NKG2A, NKG2C, NKG2D) was significantly more expressed by malignant RCDII IEL than by normal IEL in CD and RCDI. In paraffin biopsies, detection of >25 NKp46+ IEL per 100 epithelial cells discriminated RCDII from CD and RCDI. NKp46 was also detected in enteropathy-associated T-cell lymphomas (EATL, 24/29) and in monomorphic epitheliotropic intestinal T-cell lymphomas (MEITL, 4/4) but not in indolent T-LPD (0/15). Treatment with anti-NKp46-PBD could efficiently and selectively kill human NKp46+ primary IEL ex vivo . Conclusion: NKp46 is a novel biomarker useful for diagnosis and therapeutic stratification of GI T-LPD. Strong preclinical rationale identifies anti-NKp46-PBD as a promising therapy for RCDII, EATL and MEITL.